Exploration of bismuth-based nanomaterials: From fundamental concepts to innovative synthesis techniques and emerging applications - Khan, Muhammad; Sun, Xiaohui; Kashif, Muhammad; Zada, Amir; Azizi, Shohreh; Ragab, Ahmed H.; Taher, Mostafa A.; Abbas, Qumber; Shehzad, Khurram (Coordination chemistry reviews, 2025)
Bismuth-based nanoparticles have been the subject of recent scientific research due to their exceptional characteristics and diverse applications, which have sparked a new materials revolution in the nanotechnology sphere. These materials demonstrate exceptional chemical stability, low toxicity, and diverse electronics features for nemerous applications. This article thoroughly reviews the prospects of bismuth-based nanostructures and nanocomposites. A detailed information on various synthesis techniques of bismuth-based nanomaterials is provided here. The merits and demerits of each strategy are thoroughly evaluated, allowing for an in-depth knowledge of the most effective approaches. The review emphasizes the diverse uses of bismuth-based nanomaterials in medical and healthcare fields, advancement in the scaffold and regenerative solutions in tissue engineering, in the efficient degradation of toxic pollutants for environmental remediation, and in solar cells. In addition, this review provides information on the unique features of bismuth-based nanomaterials for enhancing performance and sensitivity of supercapacitors and sensors, respectively. Utilizing them in agriculture can result in enhance crop protection and increase output. This review seeks to offer significant insights to researchers and professionals, promoting innovation and sustainable progress in the growing field of nano-science and nanotechnology. •Bismuth based nanomaterials have been discussed in detail.•Merits and demerits of different synthesis techniques for Bi-based materials are provided.•Application of Bi-based materials in healthcare, and tissue engineering has been discussed.•Role of Bi-based materials in the degradation of toxic pollutants is discussed.•Applications of Bi-based materials in solar cells, supercapacitors and sensors are discussed.